ChemInform Abstract: Innovations in Sol—Gel Microextraction Phases for Solvent‐Free Sample Preparation in Analytical Chemistry. Issue 29 (1st July 2013) - Kabir, Abuzar; Furton, Kenneth G.; Malik, Abdul
Abstract: Review: 168 refs.